Effects of once weekly dual-task training in older adults: A pilot randomized controlled trial - Plummer-D'Amato, Prudence; Cohen, Zachary; Daee, Nadia A; Lawson, Sarah E; Lizotte, Marissa R; Padilla, Anna (Geriatrics & gerontology international, 2012)
Aim:  To compare single‐task and dual‐task training on obstacle avoidance, gait speed and balance in healthy community‐dwelling older adults. Methods:  A total of 17 older adults (65–83 years) participated in a group circuit class, once weekly for 45 min for 4 weeks. The dual‐task group carried out cognitive activities simultaneously with gait and balance exercises. The single‐task training group carried out identical gait and balance activities without cognitive tasks. We assessed time to complete a 6‐m obstacle course under single‐task and three different dual‐task conditions (spontaneous speech, alphabet recitation and coin transfer), 25‐ft gait speed, Timed Up and Go, and the Activities‐specific Balance Confidence Scale. Results:  Both groups showed significant improvement in gait speed and Timed Up and Go. In addition, the proportion of participants who achieved gait speed >1.0 m/s increased in both groups. There were no within‐ or between‐subjects differences in obstacle course performance under single or dual‐task conditions after the intervention. Conclusion:  Once weekly group circuit training focusing on balance, gait and agility, with or without simultaneous cognitive tasks, resulted in significantly improved walking speed among older adults. Group‐format dual‐task training once per week did not improve walking time or dual‐task cost on an obstacle negotiation task. Geriatr Gerontol Int 2012; ••: ••–••.